2014
DOI: 10.1177/1744259114532611
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of projected and actual energy performance of buildings after thermal retrofit measures

Abstract: This article addresses the discrepancies between projected and actual energy performance of thermally retrofitted buildings. Toward this end, we use detailed data and observations pertaining to seven residential buildings in Austria that were thermally retrofitted recently. These include five multifamily residences in Vorarlberg, the upper level of a duplex house in Lower-Austria, and a residential complex for the elderly in Styria. During the heating season 2009–2010 (1st October–30th April), indoor temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The characteristics reported are generally inconsistent across the studies due to differences in research foci and data availability issues. The most reported characteristics are the number of people [9,10,15,26,33,49,59,60,[79][80][81], age [9,10,15,17,21,26,33,59,77,80,81], household composition [6,7,12,14,17,30,59,77,80,82,83], and income [9,10,21,26,29,33,79,80]. Additional characteristics reported were ownership status [9,10,26,79,80,84] and education levels [17,21,…”
Section: Basic Characteristics Of Occupants In the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics reported are generally inconsistent across the studies due to differences in research foci and data availability issues. The most reported characteristics are the number of people [9,10,15,26,33,49,59,60,[79][80][81], age [9,10,15,17,21,26,33,59,77,80,81], household composition [6,7,12,14,17,30,59,77,80,82,83], and income [9,10,21,26,29,33,79,80]. Additional characteristics reported were ownership status [9,10,26,79,80,84] and education levels [17,21,…”
Section: Basic Characteristics Of Occupants In the Studiesmentioning
confidence: 99%
“…One study [85] gathered OB data through virtual reality. Similar to the occupant characteristics information, the captured behavioral information is also largely focused on residential contexts, social and student housing, and a few instances of university buildings (e.g., [5,6,9,10,[12][13][14]16,18,49,50,68,77]). The monitored behavioral information primarily relates to the number of occupants, occupancy schedule, and systems control habits concerning, for instance, operational set-points, the use of appliances and (natural or mechanical) ventilation.…”
Section: Basic Characteristics Of Occupants In the Studiesmentioning
confidence: 99%
“…Thereby, it was suggested that the frequently observed discrepancy between buildings' predicted and actual energy performance is chiefly due to simplified (typically schedulebased and rule-based) representations of inhabitants' presence and control-oriented behaviour in buildings. The relevant point of discussion here is not so much the question of if this suggestion consistently applies: In fact, a good many -but not all -discrepancies between a priori predictions of buildings' energy demand and their actual energy performance may be at least partially attributable to people's behavioural patterns (Housez, Pont, and Mahdavi 2014). Likewise, we do not wish to enter into a debate here if the principal objective of simulation studies is always the prediction of specific outcomes at specific instances of time in future (as opposed to, for example, comparative assessment of alternative design options).…”
Section: Does Simulation Matter?mentioning
confidence: 99%
“…While the UK method of approach for EPC accreditation of RDSAP employs more data, such as structure, dimensions, heating system type, levels of insulation and fenestration/lighting types, it can be expected that the default U-values incorporated within the software, though likely to be more realistic, will still incline towards the pessimistic. Housez et al (2014) are among authors of works which explore the projected and actual energy performance of buildings post-retrofit. Their study looks at seven buildings situated in Austria which have received varying depths of retrofit in an attempt to improve on thermal performance and reduce energy consumption.…”
Section: The Performance Gap Between Measurement and Modellingmentioning
confidence: 99%